2011
DOI: 10.1186/1471-2350-12-31
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and neurological characterizations of three Saudi families with lipoid proteinosis

Abstract: BackgroundLipoid proteinosis is a rare autosomal recessive disease characterized by cutaneous and mucosal lesions and hoarseness appearing in early childhood. It is caused by homozygous or compound heterozygous mutations in the ECM1 gene. The disease is largely uncharacterized in Arab population and the mutation(s) spectrum in the Arab population is largely unknown. We report the neurologic and neuroradiologic characteristics and ECM1 gene mutations of seven individuals with lipoid proteinosis (LP) from three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…The mutations in this gene lead to the deposition of a hyaline like material in the skin and the viscera in abnormal amounts, which is the cause of the clinical manifestations. These deposits stain positive with the Periodic Acid-Schiff stain and they are Diastase resistant and negative for Congo red [10].…”
Section: Case Reportmentioning
confidence: 99%
“…The mutations in this gene lead to the deposition of a hyaline like material in the skin and the viscera in abnormal amounts, which is the cause of the clinical manifestations. These deposits stain positive with the Periodic Acid-Schiff stain and they are Diastase resistant and negative for Congo red [10].…”
Section: Case Reportmentioning
confidence: 99%
“…In most genetic reports regarding LP, phenotype–genotype correlations are not obvious 8 9. Hamada and colleagues noted that individuals with mutations outside of exon 7 seemed more affected than individuals with mutations involving exon 7 of the ECM1 gene 8.…”
Section: Discussionmentioning
confidence: 99%
“…Patients from each family had skin punch biopsies including epidermis, dermis and subcutaneous tissue that were fixed in formalin and stained with PAS and PAS/diastase; in addition, laryngeal biopsies were taken from all except Patient 2B. After obtaining informed consent, the ECM1 gene was directly sequenced in affected individuals, in available first degree relatives and in 100 chromosomes from healthy individuals of matching ethnicity as described previously 3 8 9. Nucleotide numbering for mutations reported in all three families was referenced to the NCBI sequence (NG_012062).…”
Section: Methodsmentioning
confidence: 99%
“…A number of recent genetic studies reported the involvement of homozygous frame shift, missense, nonsense and single nucleotide substitution, deletion and insertion mutations in ECM1 gene LP which is located on chromosome 1q21.2 (Salih et al, 2011;Samdani et al, 2010;Kumar et al, 2009;Nasir et al, 2009). About 300 cases of LP have been so far reported.…”
Section: Discussionmentioning
confidence: 99%
“…The precise function of ECM1 is still unknown. Many pathogenic mutations have been reported so far, mostly nonsense, missense or splice site mutations with the majority occurring in exon 6 or 7 of the 10-exon in ECM1 gene encoding a glycoprotein (Salih et al, 2011). LP is histologically characterized by intercellular deposits of periodic acid Schiff (PAS)-positive hyaline material in the skin, mucous membranes and internal organs.…”
Section: Introductionmentioning
confidence: 99%